Diversity of Cercomonad Species in the Phyllosphere and Rhizosphere of Different Plant Species with a Description of Neocercomonas epiphylla (Cercozoa, Rhizaria) a Leaf‐Associated Protist. (11th February 2018) - Flues, Sebastian; Blokker, Malte; Dumack, Kenneth; Bonkowski, Michael
Abstract: Cercomonads are among the most abundant and diverse groups of heterotrophic flagellates in terrestrial systems and show an affinity to plants. However, we still lack basic knowledge of plant‐associated protists. We isolated 75 Cercomonadida strains from the phyllosphere and rhizosphere of plants from three functional groups: grasses ( Poa sp.), legumes ( Trifolium sp.) and forbs ( Plantago sp.), representing 28 OTUs from the genera Cercomonas, Neocercomonas and Paracercomonas . The community composition differed clearly between phyllosphere and rhizosphere, but was not influenced by plant species identity. From these isolates we describe three novel cercomonad species including Neocercomonas epiphylla that was consistently and exclusively isolated from the phyllosphere. For each new species we provide a detailed morphological description as well as an 18S rDNA gene sequence as a distinct marker of species identity. Our data contribute to a better resolution of the systematics of cercomonads and their association with plants, by describing three novel species and adding gene sequences of 10 new cercomonad genotypes and of nine previously described species. In view of the functional importance of cercozoan communities in the phyllosphere and rhizosphere of plants, a more detailed understanding of their composition, function and predator–prey interactions are clearly required.